2012
DOI: 10.1074/jbc.m111.292888
|View full text |Cite
|
Sign up to set email alerts
|

NEU1 Sialidase Expressed in Human Airway Epithelia Regulates Epidermal Growth Factor Receptor (EGFR) and MUC1 Protein Signaling

Abstract: Background: Airway epithelia express sialoglycoproteins that respond to danger signals and initiate repair programs. Results: NEU1 sialidase desialylates EGFR and MUC1 in airway epithelia to regulate their responsiveness to ligands and adhesiveness to P. aeruginosa. Conclusion: NEU1 provides an additional level of regulation over airway epithelial responsiveness to ligands and pathogens. Significance: The downstream effects of EGFR desialylation require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
159
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(165 citation statements)
references
References 79 publications
5
159
1
Order By: Relevance
“…AGS cells in 24-well plates were transfected with 20 pmoles/well of a MUC1-targeting small interfering RNA (siRNA) (sense, 5=-GUUCAGUGCCCAGCUCUACdTdT-3=; antisense, 5=-GUAGAGCUGGGCACUGAACdTdT-3=) or with a nontargeting control siRNA (sense, 5=-GCGCGCUUUGUAGGAUUCGdTdT-3=; antisense, 5=-CGAAUCCUACAAAGCGCGCdTdT-3=) (Dharmacon, Lafayette, CO), using 2.0 l/well of Lipofectamine (Invitrogen) as described (18). Prior studies have documented the specificity of the MUC1 siRNA with no demonstrable off-target effects (18,23,30,32,33,35).…”
Section: Methodsmentioning
confidence: 99%
“…AGS cells in 24-well plates were transfected with 20 pmoles/well of a MUC1-targeting small interfering RNA (siRNA) (sense, 5=-GUUCAGUGCCCAGCUCUACdTdT-3=; antisense, 5=-GUAGAGCUGGGCACUGAACdTdT-3=) or with a nontargeting control siRNA (sense, 5=-GCGCGCUUUGUAGGAUUCGdTdT-3=; antisense, 5=-CGAAUCCUACAAAGCGCGCdTdT-3=) (Dharmacon, Lafayette, CO), using 2.0 l/well of Lipofectamine (Invitrogen) as described (18). Prior studies have documented the specificity of the MUC1 siRNA with no demonstrable off-target effects (18,23,30,32,33,35).…”
Section: Methodsmentioning
confidence: 99%
“…NEU3 was the second most abundant EC sialidase found at the mRNA level. When airway epithelia were assayed for sialidase activity for ganglioside substrates, SA release was evident (31), suggesting that the Ϸ30% residual sialidase activity detected in airway epithelia after NEU1 silencing might be explained, in part, through NEU3 enzymatic activity. Accordingly, in the present study we surveyed a diverse collection of human airway ECs for sialidase activity against ganglioside substrates, identified NEU3 mRNA and protein in these same epithelia, as well as in intact human airway tissues, and correlated siRNA-induced knockdown of NEU3 expression with reduced ganglioside-directed sialidase activity.…”
mentioning
confidence: 99%
“…In recent studies in human airway epithelia, we found heat-labile sialidase activity for the fluorogenic substrate, 2=-(4-methylumbelliferyl)-␣-D-Neu5Ac (4-MU-Neu5Ac), that was dose dependently inhibited by the sialidase inhibitor, 2-deoxy-Neu5Ac, but not its negative control, 2-keto-3-deoxyoctulosonic acid (31). These airway epithelia expressed predominantly NEU1 sialidase at the mRNA and protein levels, and small interfering (si)RNA-induced silencing of NEU1 diminished sialidase activity for the 4-MUNeu5Ac substrate Ͼ70% compared with control siRNA-transfected ECs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lillehoj et al reported sialidase activity in human airway epithelial cells derived from lysosomal neuraminidase (NEU1) (57). Clostridium perfringens neuraminidase, which is highly homologous to NEU1 (58), was unable to support SIV/606 replication in vitro (data not shown), possibly because the neuraminidase activity of Clostridium perfringens has optimal pH and calcium ion requirements different from those of Vibrio cholerae (59).…”
Section: Discussionmentioning
confidence: 99%